Model of Application of Technology to Increase Income in Micro Business Clover Stick in The Face of Covid19 Pandemic Era - Hendrik Rizqiawan; Iful Novianto; Subaderi Subaderi (Procedia of Social Sciences and Humanities, 2021)
The Covid19 pandemic has caused complicated problems for many entrepreneurs, including partners who are micro-entrepreneurs. The Semanggi Stick micro business, which is run by a group of women in Lakarsantri Village, Surabaya City, has been severely affected by the Covid19 pandemic. Even in the first few months of the pandemic outbreak, their businesses did not operate. The clover sticks they produce are not the main choice that must be purchased for communities around the partner’s location. This is possible because so far partners have only marketed their products around their area, partners have not taken advantage of the availability of digital technology in marketing. In addition, partners have been carrying out the production process using conventional and simple equipment. This was considered ineffective and resulted in some partner members choosing other activities that were more productive. With the right technology application model, both in the production and marketing processes, partners will experience an increase in sales. Before the pandemic, the sales generated by partners was at 500 thousand to 1 million per month, after using this technology application model partners can get a sales of more than 2 million Rupiah in one month.